Structural and Cultural Aspects of Fisherman Family Education Problems in Waruduwur Cirebon - Syatori, A; Ramdhani, Suciyadi; Khikmawati, Nurlaili (Masyarakat: Jurnal Sosiologi, 2023)
According to the Program for International Student Assessment (PISA), Indonesia's education quality is ranked 74th out of 79 countries. The data highlights issues including high tuition costs, unequal access to educational institutions, as well as mismatch between education system and local culture; all commonly found in fishing communities. This ethnographic study seeks to investigate cultural and structural factors that affect the lagging education of children of fishermen in Waruduwur village, Cirebon, West Java, Indonesia. The findings indicate that both factors are interlinked, significantly shaping collective views on education as well as children’s participation in schooling. Patterns observed in the study allow categorization of families by scrutinizing their position between two axes: income and views on education. By seeing the combinations, four groups can be inferred: (1) families inclined towards education and earning middle income; (2) middle-income families that do not prioritize education; (3) low-income families that emphasize education; and (4) low-income families that do not focus on education. They reflect the varying degrees of challenges but also point to the significance of cultural intervention, which has been partially addressed through the establishment of informal education institutions in Waruduwur.